An Integrated Career Coaching and Time-Banking System Promoting Flexibility, Wellness, and Success: A Pilot Program at Stanford University School of Medicine. (June 2018) - Fassiotto, Magali; Simard, Caroline; Sandborg, Christy; Valantine, Hannah; Raymond, Jennifer
Abstract : Faculty in academic medicine experience multiple demands on their time at work and home, which can become a source of stress and dissatisfaction, compromising success. A taskforce convened to diagnose the state of work–life flexibility at Stanford University School of Medicine uncovered two major sources of conflict: work–life conflict, caused by juggling demands of career and home; and work–work conflict, caused by competing priorities of the research, teaching, and clinical missions combined with service and administrative tasks. Using human-centered design research principles, the 2013–2014 Academic Biomedical Career Customization (ABCC) pilot program incorporated two elements to mitigate work–life and work–work conflict: integrated career–life planning, coaching to create a customized plan to meet both career and life goals; and a time-banking system, recognizing behaviors that promote team success with benefits that mitigate work–life and work–work conflicts. A matched-sample pre–post evaluation survey found the two-part program increased perceptions of a culture of flexibility ( P = .020), wellness ( P = .013), understanding of professional development opportunities ( P = .036), and institutional satisfaction ( P = .020) among participants. In addition, analysis of research productivity indicated that over the two-year program, ABCC participants received 1.3 more awards, on average, compared with a matched set of nonparticipants, a funding difference of approximately 1.1 million per person. These results suggest it is possible to mitigate the effects of extreme time pressure on academic medicine faculty, even within existing institutional structures. Abstract : Supplemental Digital Content is available in the text.